Analisis Diskursus: Pasangan Ujaran Sepadan dalam Video YouTube Korean Englishman yang Terpilih - Salsa Alifia Iskandar; Meita Lukitawati Sujatna (Linguistic, English Education and Art (LEEA) Journal, 2024)
This research focuses to analyze adjacency pairs in the selected Korean Englishman YouTube Video titled “K-Pop Idol NCT Johnny fed us luxury Korean Beef BBQ!” using Yule’s (1996) theory. This study is using the qualitative descriptive method to analyze the data. From the conversation uttered by speakers, there are some patterns that they automatically produced, called adjacency pairs. The adjacency pairs occur when two or more people talk and respond to each other’s questions. Based on the analysis, there are 25 adjacency pairs; (15) Question–Answer, (1) Command–Compliance, (1) Request–Acceptance, (1) Offer–Acceptance, (5) Assessment–Agreement, (2) Suggestion–Acceptance that were found in the conversation between Johnny, Josh, and Ollie in the Korean Englishman YouTube video titled “K-Pop Idol NCT Johnny fed us luxury Korean Beef BBQ!”. From all the data found in this study, the functions of utterances are in accordance with each type of adjacency pair thus conclude that adjacency pairs are automatic sequences of two utterances produced by two speakers with the second utterances conversing about the first utterance. Key Words: Adjacency Pairs, Conversation Analysis, Discourse Analysis